2011
DOI: 10.4103/0972-2327.82796
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomal myeloradiculopathy due to Schistosoma mansoni: Report on 17 cases from an endemic area

Abstract: Background:After malaria, schistosomiasis is the second most prevalent tropical disease. The prevalence of oviposition in CNS of infected persons varies from 0.3 to 30%. The conus medullaris is a primary site of schistosomiasis, either granulomatous or acute necrotizing myelitis.Objective:To report the clinical, radiological, and laboratory results of spinal cord schistosomiasis (SCS) and to design proper therapeutic regimens.Materials and Methods:Seventeen patients (13 males and four females) with SCS were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…Epilepsy can be caused by schistosomiasis [58]. In Egypt, schistosomiasis due to Schistosoma mansoni of the spinal cord is considered the primary cause of the parasitic invasion of the spinal cord [59]. Neurological involvement usually occurs within weeks or months after infection when eggs migrate via the vascular system to the spinal cord or the brain.…”
Section: Schistosomamentioning
confidence: 99%
“…Epilepsy can be caused by schistosomiasis [58]. In Egypt, schistosomiasis due to Schistosoma mansoni of the spinal cord is considered the primary cause of the parasitic invasion of the spinal cord [59]. Neurological involvement usually occurs within weeks or months after infection when eggs migrate via the vascular system to the spinal cord or the brain.…”
Section: Schistosomamentioning
confidence: 99%
“…45 Corticosteroids reduce the immune response, hence prevent excessive granulomatous inflammation and tissue damage. 44,46,47 Clinical trials are required to test the effect of corticosteroids in the treatment of schistosomiasis. However, case reports indicate a beneficial effect of their use in combination with praziquantel and other antischistosomal drugs.…”
Section: Introductionmentioning
confidence: 99%
“…3 There is no consensus regarding the length of steroid treatment in the literature, however there is evidence that it should be done for more than two months and, if discontinued before six months increases the risk of symptom relapse. 3, 10 Badr, in a report of 17 patients with SMR in Egypt, reported that among patients who discontinued the corticosteroids early on (less than 60 days of use), 75% had recurrent symptoms of myelopathy. 10 Andrade, analyzing 16 SMR patients treated with praziquantel 60 mg/kg/day for three days in combination with prednisone 100 mg/day, showed that improvement in the symptoms was observed starting from the first two weeks of treatment.…”
mentioning
confidence: 99%
“…3, 10 Badr, in a report of 17 patients with SMR in Egypt, reported that among patients who discontinued the corticosteroids early on (less than 60 days of use), 75% had recurrent symptoms of myelopathy. 10 Andrade, analyzing 16 SMR patients treated with praziquantel 60 mg/kg/day for three days in combination with prednisone 100 mg/day, showed that improvement in the symptoms was observed starting from the first two weeks of treatment. The regression speed varied according to each patient.…”
mentioning
confidence: 99%
See 1 more Smart Citation